Comparison of Kriging and Inverse Distance Weighted (IDW) Interpolation Methods in Lineament Extraction and Analysis - Agung Setianto, Agung Setianto (2013)
Analysis that is based on geostatistics eliminates many corresponding defects and limitations compared to classical statistic which have been developed by random distribution theory of processes and variables. Interpolation is important for local analysis by GIS, because many maps used for GIS operation are made by interpolation. In this research, two different methods which is Kriging method and Inverse Distance Weighted (IDW) method was examined for developing Digital Elevation Model image. Each method's advantages and disadvantages were considered.